Weimar surfaces : urban visual culture in 1920s Germany - Ward, Janet, 1963- (Weimar and now, 2001)
This study revisits Weimar Germany via the lens of metropolitan visual culture, analyzing the power that 1920s Germany holds for today's visual codes of consumerism.